The data-driven leader: developing a big data analytics leadership competency framework - Schmidt, David Holger; van Dierendonck, Dirk; Weber, Ulrike (The Journal of management development, 2023)
PurposeThis study focuses on leadership in organizations where big data analytics (BDA) is an essential component of corporate strategy. While leadership researchers have conducted promising studies in the field of digital transformation, the impact of BDA on leadership is still unexplored.Design/methodology/approachThis study is based on semi-structured interviews with 33 organizational leaders and subject-matter experts from various industries. Using a grounded theory approach, a framework is provided for the emergent field of BDA in leadership research.FindingsThe authors present a conceptual model comprising foundational competencies and higher order roles that are data analytical skills, data self-efficacy, problem spotter, influencer, knowledge facilitator, visionary and team leader.Research limitations/implicationsThis study focuses on BDA competency research emerging as an intersection between leadership research and information systems research. The authors encourage a longitudinal study to validate the findings.Practical implicationsThe authors provide a competency framework for organizational leaders. It serves as a guideline for leaders to best support the BDA initiatives of the organization. The competency framework can support recruiting, selection and leader promotion.Originality/valueThis study provides a novel BDA leadership competency framework with a unique combination of competencies and higher order roles.